A high-throughput ultra-thin polyamide nanofiltration membrane and preparation method thereof
The two-dimensional polymer mesh-like polyamide selective separation layer prepared by low-temperature interfacial polymerization method solves the problem of low nanofiltration membrane performance and achieves high throughput and high selectivity water treatment effects.
Patent Information
- Application Number
- CN202211494490.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-11-25
AI Technical Summary
The existing nanofiltration membranes have low performance in terms of permeability and selectivity, and the polyamide layer formed by traditional interface polymerization processes is multi-scale heterogeneity and unstable performance, making it difficult to achieve a high-performance water treatment membrane.
The polyamide selective separation layer with a two-dimensional polymer network structure is prepared by low-temperature interfacial polymerization method in the organic solvent-water/ice interface greening. By adjusting the diffusion and reaction conditions of the amine monomer, the surface is smoother and the flux is formed. High performance film with smaller thickness.
It realizes efficient interception of salt ions and dyes in water, and at the same time improves the permeability of water molecules, which improves 2-5 times compared to traditional membranes, and has a simple and easy process.
Smart Images

Figure HDA0003965058730000011 
Figure HDA0003965058730000012 
Figure HDA0003965058730000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and particularly relates to a high-flux ultra-thin polyamide nanofiltration membrane and a preparation method thereof. Background Art
[0002] Water shortages caused by population explosion and environmental pollution pose a huge challenge to the sustainable development of the global economy and society. Therefore, we must achieve effective and sustainable freshwater supply through technological innovation to meet this global challenge. Among all existing water treatment technologies, emerging membrane-based separation technologies, such as reverse osmosis (RO) and nanofiltration (NF), are the most energy-efficient and environmentally friendly, while traditional chemical engineering processes, such as distillation, adsorption and extraction, suffer from high energy consumption, large footprint, and high capital and operating costs. In particular, nanofiltration technology that uses molecular sieve effect and Donan effect to intercept multivalent salts and organic molecules with (MWCO)>200Da has become an ideal water treatment technology.
[0003] The most advanced NF membranes currently used for a wide range of applications such as desalination and antibiotic concentration are thin film composite (TFC) membranes, which consist of a polyamide (PA) active layer and a porous support substrate, typically a microfiltration (MF) or ultrafiltration (UF) membrane. This TFC structure produces high-performance NF membranes with strong mechanical properties, but the water permeability, which determines the economic and production benefits of NF membranes, is still low. The nanofiltration performance of TFC membranes in terms of permeability and selectivity is mainly determined by the PA active layer formed by interfacial polymerization (IP), which is also the cutting-edge method for commercial membrane manufacturing. In a typical IP process, amine monomers in the aqueous phase and acyl chloride monomers in the organic phase diffuse to the interface separately, and once they arrive, the Scotten-Bauman reaction occurs rapidly. This traditional interfacial polymerization process forms a PA layer with multi-scale heterogeneity and unstable performance, and controllable interfacial polymerization should be further studied to obtain high-performance polyamide membranes.
[0004] Interfacial polymerization is an exothermic reaction controlled by diffusion reaction, and the diffusion rate of amine monomer determines the reaction rate. By controlling the IP process, we aim to improve the performance. One feasible strategy is to control the release of amine monomer by adding an intermediate layer, such as inorganic nanowires, carbon nanolayers, and polymer layers. The main principle of this strategy is to make the distribution of amine solution more uniform and release monomer more effectively during IP process by enhancing the hydrophilicity and uniformity of porosity of substrate surface. However, the removal of intermediate layer after IP is not conducive to the composite strength of PA layer and substrate surface and makes the preparation process relatively complicated. If the intermediate layer is not removed, the nanoparticles are reported to be environmentally unfriendly and harmful to human body, which limits their practical application in water treatment. Another strategy to control the diffusion of amine monomer is to adjust the solution properties by adding additives, such as surfactants and polymer macromolecules. The dynamic, self-assembled network of surfactants is conducive to the rapid and more uniform diffusion of amine monomers, thus forming a PA active layer with more uniform sub-nanopores. The addition of macromolecular polymers that interact with amine monomers through hydrogen bonds increases the solution viscosity and reduces the diffusion rate of monomers, forming a highly permeable PA membrane with Turing structure. However, both strategies to control monomer diffusion by external rather than internal means may undermine compatibility. More importantly, heat, as a core factor affecting diffusion and reaction during IP, has been rarely studied. Ben et al. intuitively observed that heat released by IP can lead to interfacial boiling or release of dissolved gases, resulting in the formation of voids in the membrane. Therefore, heat control is necessary because its transfer directly affects the structure and properties of the membrane.
[0005] Here, we view IP from the perspective of chemical engineering as a coupled process of "mass transfer-heat transfer-reaction", where the molecular diffusion of monomers is mass transfer, the conduction of reaction heat is heat transfer, and the polymerization reaction is the reaction process of monomers. We believe that the above three should be coordinated in the contemporary era to obtain a fully controllable interfacial polymerization process. Therefore, the present invention proposes a non-isothermal interfacial polymerization method, which effectively controls the three processes by adjusting the inherent temperature to form a high-performance membrane with a smoother surface, higher flux and smaller thickness. Summary of the invention
[0006] The key technical problem to be solved by the present invention is to provide a method for preparing a high-throughput ultra-thin polyamide nanofiltration membrane, so that the prepared thin-layer water treatment composite membrane has a good effect on removing salt ions and dyes in water, and at the same time has an ultra-high permeation flux. The specific technical solution is as follows:
[0007] In a first aspect, the present invention provides a high-flux ultrathin polyamide nanofiltration membrane, comprising a porous base membrane and a polyamide selective separation layer in situ grown on the surface of the porous base membrane;
[0008] The polyamide selective separation layer is a two-dimensional polymer network structure prepared by green polymerization at an organic solvent-water / ice interface using low-temperature interfacial polymerization, and has a super selective separation effect on salt ions and dye molecules.
[0009] Preferably, the polyamide selective separation layer structure includes one or more structures of polypiperazineamide (--N-CO-), polyamide (-NH-CO-), and polyimide (-CO-N-CO-);
[0010] Specifically, the thickness of the polyamide selective separation layer is 10nm to 100nm.
[0011] Specifically, the porous base membrane is selected from an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and has an average pore size of 0.001-100 μm;
[0012] Specifically, the porous base membrane may be in the form of a flat plate, a tube or a hollow fiber.
[0013] In a second aspect, the present invention provides a method for preparing the composite film, comprising:
[0014] Step a, washing the surface of the porous substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0015] Step b, dissolving a certain amount of amine monomer in deionized water, and stirring until a transparent uniform solution is obtained; dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained;
[0016] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in an aqueous solution of amino monomers for a period of time to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a low-temperature chamber, take it out after a period of time and immediately immerse it in an acyl chloride solution, and after reacting for a period of time, immerse it in an organic solvent to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane.
[0017] Specifically, the organic and inorganic solvents described in step a are selected from at least one of methanol, ethanol, benzene, toluene, ether, and deionized water;
[0018] Specifically, the amino monomer described in step b is preferably: one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, polyethyleneimine, ethylenediamine, hexamethylenediamine, and diethylenetriamine; the acyl chloride monomer is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyltetrachloride, biphenylhexachloride, and 1,5-naphthalene disulfonyl chloride; the concentrations of the amino and acyl chloride monomers are both 0.1-5wt%; the stirring time of the amino monomer aqueous solution and the acyl chloride solution is 0.5-6h.
[0019] Specifically, the organic solvent in step b is selected from at least one of n-hexane, benzene and toluene.
[0020] The temperature of the low temperature chamber in step c is room temperature which is lower than the temperature of the aqueous solution of the amino monomer and the temperature of the acyl chloride solution, preferably 0 to -20°C, more preferably 0 to -10°C. The low temperature chamber can be a refrigerator or a freezer, and is cooled by air medium.
[0021] The technical solution provided by the present invention has the following beneficial effects: the present invention in situ grows a selective separation layer with a two-dimensional network structure on a porous base membrane. The formed separation layer is ultra-thin and can intercept a variety of salt ions and dye molecules, while allowing water molecules to pass quickly, and the permeation flux of the membrane is 2-5 times higher than that of a traditional polyamide nanofiltration membrane. In addition, the method of the present invention is simple and easy to implement, and the two-dimensional network separation layer can be uniformly grown on the surface of a variety of substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 . Transmission electron microscopy images of the surface of the high-throughput ultra-thin polyamide nanofiltration membrane (1-1) and (1-2) prepared in Example 1 of the present invention.
[0023] Figure 2 . Transmission electron microscopy images of the surface (2-1) and cross-section (2-2) of the high-throughput ultrathin polyamide nanofiltration membrane prepared in Example 2 of the present invention.
[0024] Figure 3 . Transmission electron microscopy images of the surface (3-1) and cross-section (3-2) of the high-throughput ultrathin polyamide nanofiltration membrane prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0025] To make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings, but the present invention is not limited to the following embodiments.
[0026] In a first aspect, the present invention provides a high-performance thin-layer water treatment composite membrane, comprising a porous base membrane and a polyamide selective separation layer in-situ grown on the surface of the porous base membrane;
[0027] The polyamide selective separation layer is a two-dimensional polymer network structure prepared by greening at an organic solvent-water / ice interface using a low-temperature method, and has a super selective separation effect on salt ions and dye molecules.
[0028] Preferably, the polyamide selective separation layer structure includes one or more of the structures of polypiperazineamide (--N-CO-), polyamide (-NH-CO-), and polyimide (-CO-N-CO-);
[0029] Specifically, the thickness of the polyamide selective separation layer is 10nm to 100nm.
[0030] Specifically, the porous base membrane is selected from an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and has an average pore size of 0.001-100 μm;
[0031] Specifically, the porous base membrane may be in the form of a flat plate, a tube or a hollow fiber.
[0032] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned composite film, comprising:
[0033] Step a, washing the surface of the porous substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0034] Step b, dissolving a certain amount of amino monomer in deionized water, and stirring until a transparent and uniform solution is obtained; dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent and uniform solution is obtained.
[0035] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in an aqueous solution of amino monomers for a period of time to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a low-temperature chamber at a certain temperature, take it out after a certain period of time and immerse it in an acyl chloride solution, and after reacting for a period of time, immerse it in an organic solvent to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane.
[0036] Specifically, the organic and inorganic solvents described in step a are preferably at least one of methanol, ethanol, benzene, toluene, ether, and deionized water.
[0037] Specifically, the amino monomer in step b is preferably selected from one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, polyethyleneimine, ethylenediamine, hexamethylenediamine, and diethylenetriamine. The acyl chloride monomer is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyl tetrachloride, biphenyl hexachloride, and 1,5-naphthalene disulfonyl chloride; the concentrations of the amino and acyl chloride monomers are both 0.1-5wt%; the stirring time of the amino monomer aqueous solution and the acyl chloride solution is 0.5-6h.
[0038] Specifically, the organic solvent in step b is selected from at least one of n-hexane, benzene and toluene.
[0039] The present invention will be further described below through specific examples.
[0040] In the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained from the market.
[0041] Example 1
[0042] A polyethersulfone (PES) porous base membrane is used, and the average pore size of the base membrane is 0.05um; the low temperature chamber temperature is selected to be -20°C.
[0043] Step a, washing the surface of the porous substrate with ethanol aqueous solution for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0044] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, and stirring until a transparent uniform solution is obtained; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained.
[0045] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a -20°C low-temperature chamber, take it out after 30 minutes and immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in a n-hexane solution for 30 seconds to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane.
[0046] SEM photos ( Figure 1 )The surface of the high-throughput ultra-thin polyamide nanofiltration membrane is dense, without pinholes and obvious defects, and the thickness of the selective separation layer is about 20.07nm.
[0047] The prepared composite membrane was placed in a membrane performance evaluation device for performance testing. The test conditions were: the stock solution composition was 1g / L Na2SO4 water system
[0048] The performance of the composite membrane was measured as follows: Na2SO4 rejection was 96.58% and permeation flux was 27.5 LMH / bar.
[0049] Example 2
[0050] A polyethersulfone (PES) porous base membrane is used, and the average pore size of the base membrane is 0.05 um; the temperature of the low temperature chamber is selected to be 0°C.
[0051] Step a, washing the surface of the porous substrate with ethanol aqueous solution for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0052] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, and stirring until a transparent uniform solution is obtained; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained.
[0053] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a 0°C low-temperature chamber, take it out after 30 minutes and immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in a n-hexane solution for 30 seconds to remove unreacted acyl chloride monomers, so that a high-throughput ultra-thin polyamide nanofiltration membrane can be obtained.
[0054] SEM photos ( Figure 1 ) The surface of the high-throughput ultra-thin polyamide nanofiltration membrane is dense, without pinholes and obvious defects, and the thickness of the selective separation layer is about 24nm.
[0055] The prepared composite membrane was placed in a membrane performance evaluation device for performance testing. The test conditions were: the stock solution composition was 1g / L Na2SO4 water system.
[0056] The performance of the composite membrane was measured as follows: Na2SO4 rejection was 97.19% and permeation flux was 33.05 LMH / bar.
[0057] Example 3
[0058] A polyacrylonitrile (PAN) porous base membrane is used, and the average pore size of the base membrane is 0.05um; the temperature of the low-temperature chamber is selected to be 0°C.
[0059] Step a, washing the surface of the porous substrate with ethanol aqueous solution for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0060] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, and stirring until a transparent uniform solution is obtained; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained.
[0061] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a 0°C low-temperature chamber, take it out after 30 minutes and immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in a n-hexane solution for 30 seconds to remove unreacted acyl chloride monomers, so that a high-throughput ultra-thin polyamide nanofiltration membrane can be obtained.
[0062] SEM photos ( Figure 1 )The surface of the high-throughput ultra-thin polyamide nanofiltration membrane is dense, without pinholes and obvious defects, and the thickness of the selective separation layer is about 22nm.
[0063] The prepared composite membrane was placed in a membrane performance evaluation device for performance testing. The test conditions were: the stock solution composition was 1g / L Na2SO4 water system.
[0064] The performance of the composite membrane was measured as follows: Na2SO4 rejection was 97% and permeation flux was 30.28 LMH / bar.
[0065] Example 4
[0066] A polyethersulfone (PES) porous base membrane is used, and the average pore size of the base membrane is 0.02um; the low temperature chamber temperature is selected to be -20°C.
[0067] Step a, washing the surface of the porous substrate with ethanol aqueous solution for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0068] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, and stirring until a transparent uniform solution is obtained; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained.
[0069] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a -20°C low-temperature chamber, take it out after 30 minutes and immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in a n-hexane solution for 30 seconds to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane.
[0070] The prepared composite membrane was placed in a membrane performance evaluation device for performance testing. The test conditions were: the stock solution composition was 1g / L Na2SO4 water system.
[0071] The performance of the composite membrane was measured as follows: Na2SO4 rejection was 99.21% and permeation flux was 19.23 LMH / bar.
[0072] Example 5
[0073] A polyethersulfone (PES) porous base membrane is used, and the average pore size of the base membrane is 0.02um; the low temperature chamber temperature is selected to be -10°C.
[0074] Step a, washing the surface of the porous substrate with ethanol aqueous solution for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0075] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, and stirring until a transparent uniform solution is obtained; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained.
[0076] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution, then transfer the membrane to a -10°C low-temperature chamber, take it out after 30 minutes and immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in a n-hexane solution for 30 seconds to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane.
[0077] The prepared composite membrane was placed in a membrane performance evaluation device for performance testing. The test conditions were: the stock solution composition was 1g / L Na2SO4 water system.
[0078] The performance of the composite membrane was measured as follows: Na2SO4 rejection rate was 99.06% and permeation flux was 21.7LMH / bar.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance thin-layer water treatment composite membrane, comprising a porous base membrane and a polyamide selective separation layer in situ grown on the surface of the porous base membrane, characterized in that: The polyamide selective separation layer is a two-dimensional polymer network structure prepared by low-temperature interfacial polymerization at an organic solvent-water / ice interface; The polyamide selective separation layer structure includes one or more of the structures of polypiperazineamide (-N-CO-), polyamide (-NH-CO-), and polyimide (-CO-N-CO-); The preparation method comprises the following steps: Step a, washing the surface of the porous substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, and rinsing the surface solvent with deionized water and storing it in deionized water for later use; Step b, dissolving a certain amount of amine monomer in deionized water, and stirring until a transparent uniform solution is obtained; dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent uniform solution is obtained; Step c, wiping off the water droplets on the surface of the porous base membrane in step a, and placing it in an aqueous solution of amine monomers for a period of time to make the membrane surface and pores rich in amine molecule solution, and then transferring the membrane to a low temperature chamber, taking it out after a period of time and immersing it in an acyl chloride solution, and after reacting for a period of time, immersing it in an organic solvent to remove unreacted acyl chloride monomers, so as to obtain a high-throughput ultra-thin polyamide nanofiltration membrane; The temperature of the low-temperature chamber in step c is lower than the temperature of the amino monomer aqueous solution and the temperature of the acyl chloride solution, and the temperature is -20°C to 0; The amino monomer described in step b is selected from: one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, polyethyleneimine, ethylenediamine, hexamethylenediamine, and diethylenetriamine; the acyl chloride monomer is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyltetrachloride, biphenylhexachloride, and 1,5-naphthalene disulfonyl chloride; the concentrations of the amino and acyl chloride monomers are both 0.1-5 wt%; the stirring time of the amino monomer and the ultrasonic time of the acyl chloride monomer are both 0.5-6 h.
2. The method for preparing a high-performance thin-layer water treatment composite membrane according to claim 1, characterized in that: The thickness of the polyamide selective separation layer is 20 nm to 100 nm.
3. The method for preparing a high-performance thin-layer water treatment composite membrane according to claim 1, characterized in that: The porous base membrane is selected from an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and has an average pore size of 0.001-100 μm.
4. The method for preparing a high-performance thin-layer water treatment composite membrane according to claim 1, characterized in that: The porous base membrane is in the shape of a flat plate, a tube or a hollow fiber.
5. The method for preparing a high-performance thin-layer water treatment composite membrane according to claim 1, characterized in that: The organic and inorganic solvents described in step a are selected from at least one of methanol, ethanol, benzene, toluene, ether, deionized water, liquid ammonia, and acetic acid; The organic solvent described in step b is at least one selected from n-hexane, benzene and toluene.
6. The method for preparing a high-performance thin-layer water treatment composite membrane according to claim 1, characterized in that: The temperature of the low-temperature chamber in step c is -10°C to 0, and the low-temperature chamber can be a refrigerator or a freezer, and is cooled by air medium.
7. A high-performance thin-layer water treatment composite membrane prepared according to the method described in any one of claims 1 to 6.
8. Application of a high-performance thin-layer water treatment composite membrane prepared by the method according to any one of claims 1 to 6: used in seawater desalination, sewage purification, dye desalination, and wastewater treatment.
Citation Information
Patent Citations
High-flux composite membrane preparation method
CN105289335A
Positively charged composite nano filtration membrane and preparation method
CN109794166A
Preparation method of hollow fiber nano-filtration membrane
CN111054219A
Structure-controllable composite nanofiltration membrane and preparation method thereof
CN113304611A
Composite semipermeable membrane and method of producing the same
US20120305473A1
